Implementasi Dan Analisis Sistem Informasi Manajemen Data Mahasiswa Berbasis Web - Berliani Salsabiilah; Athaya Rima Hariyanto (PT Jurnal Cendekia Indonesia, 2025)
This research focuses on the development and implementation of a web-based Student Data Management Information System. The goal is to support more effective, organized, and accurate data management. The system was developed using the Waterfall method, which includes the stages of requirement analysis, design, implementation, testing, and maintenance. Black Box Testing was used during the testing phase to ensure that each system function operates as expected by the user, without examining the internal code. The test results show that all key features—such as login, data input, editing, deletion, search, and logout—function properly. It is expected that this system will speed up administrative services and minimize errors in managing student data.